PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA DIMSUM BANG ADWA DI TANGERANG SELATAN - Anisa Ayu Oktarina; Fauziah Septiani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to determine the effect of product quality on the purchase decision of dimsum bang adwa in south tangerang partially. to determine the effect of price on the purchase decision of dimsum bang adwa in south tangerang partially. to determine the effect of product quality and promotion on the purchase decision of dimsum bang adwa in south tangerang simultaneously. this research method uses a quantitative description method, data collection techniques using questionnaires. the population is 12,284 consumers, sampling can use saturated sampling, so the sample is all employees totaling 99 consumers. data analysis uses validity test, reliability test, classical assumption test, multiple regression analysis, multiple correlation coefficient analysis, determination coefficient analysis and hypothesis test, there is an effect of product quality (x1) with a t count of 4.669 and a significance of 0.000. because t count is greater than t table (4.669> 1.984) and the significance is less than 5% then ha is accepted and h0 is rejected, it can be stated that product quality (x1) has a significant effect on consumer satisfaction (y). there is an influence of promotion (x2) with a t count of 7.531 and a significance of 0.000. because t count is greater than t table (7.531 > 1.984) and the significance is less than 5% (0.000) then ha is accepted and h0 is rejected, it can be stated that promotion (x2) has a significant effect on consumer satisfaction (y). there is a significant influence between product quality and price on consumer satisfaction. based on the results of the analysis in the table above, namely the anova test, the f count value is 76.718 while f table (฀ 0.05) for n = 96 is 2.70. so f count> from f table (฀ 0.05) or 76.718> 2.70, with a significance level of 0.000 because 0.000 <0.05, it can be said that product quality (x1), promotion (x2) and together have an effect on consumer satisfaction (y).